HGG-19. ETV5 EXPRESSION AND FUNCTION IN PEDIATRIC GLIOMA - Park, Hannah (Neuro Oncol, 2017)
Pediatric gliomas, a type of brain tumor which arises from uncontrolled growth of glial cells, are the most common type of CNS tumor in children. As the list of putative driver mutations in glioma grows, we are just beginning to elucidate the combined effects of unhinged signaling pathways on the transformation of CNS cells. While the oncogenic role of ETV5 in various cancers is well-established, its role in high-grade pediatric gliomas has yet to be elucidated. We have created a mosaic, autochthonous, glioma model that captures the first hours and days of gliomagenesis in more resolution than conventional mouse models of cancer. Our various models of pediatric glioma have indicated a fundamental role for Etv5 in tumor cells. We show that ETV5 is highly expressed in our glioma models and primary pediatric glioma cells. We are currently pursuing an omics approach to identifying the mechanisms regulating ETV5 in high-grade glioma. Additionally, we are employing a novel single-site conditional system to identify ETV5 genomic targets in patient tumors and to explore the results of ETV5 manipulation on cell fate. Taken together, we provide evidence that Etv5 is necessary for tumor initiation and regulates the exuberant gliogenesis observed in these tumors.